Teoria della nascita e castrazione umana alla Festa dell’Unità. Roma, 7 luglio 2012 - Vari, Autori (Il sogno della farfalla, 2013)
For the third consecutive year the Festa dell’Unità of Roma, an event organized by the Democratic Party every summer, hosted the presentation of a book by Massimo Fagioli: in this particular case, Teoria della nascita e castrazione umana (The theory of birth and human castration), now published by L’Asino d’oro edizioni, which completes the trilogy originally published by the author in 1972-75. The speeches delivered by G. Santilli and the psychiatrists and psychotherapists E. Pappagallo, M. Reggio d’Aci, V. Righetti, A. Masillo and L. Cancrini, followed by the author’s comment, connect back to the other presentations already published in this magazine (4/2012) and illustrate the fundamental contents of the book, its position in the life of the author and the history of the Collective Analysis, the political implications of a theory and practice founded on the equality of human beings at birth.